(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2020)
The high bit error rate of the wireless communications system requires forward error correction (FEC) methods to be implemented on the data to be transmitted. Orthogonal Frequency Division Multiplexing (OFDM) technique exhibits some challenges which are Inter Carrier Interference (ICI), Peak to Average Power Ratio (PAPR) and inadequate spectral efficiency at higher subcarrier channels. Many researchers have attempted to mitigating the above mentioned challenges by using different error coding techniques. Therefore, this paper evaluated the performance of convolutional, Reed-Solomon and concatenated coding schemes over AWGN and Rayleigh fading channels in order to improve the spectral efficiency at higher subcarriers. The concatenated scheme was implemented in MATLAB R2015b environment and simulation result was validated by comparing the coding techniques with the uncoded OFDM signal using Bit Error Rate (BER) and Signal to Interference Ratio (SIR) as performance. Â